Pemanfaatan Teknologi Komputasi untuk Solusi Permasalahan Masyarakat di Bandar Lampung - Hartanto, M. Budi; Fahurian, Fatimah (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
This community service activity aims to apply computational technology as a solution to various problems faced by the community in Bandar Lampung City. The identified issues include low digital literacy, limited use of software for economic activities, and the need for simple information systems to support local initiatives. The implementation method involved basic computational training, development of simple applications based on local needs, and mentoring in digital technology utilization. The results showed an improvement in participants’ ability to use computational tools, understand basic programming concepts, and apply technology to increase efficiency and productivity in daily activities. The implications indicate that the application of computational technology has significant potential to empower communities and strengthen digital transformation at the local level.